Puberty suppression in adolescents with gender dysphoria: an emerging issue with multiple implications - Betsi, Grigoria; Goulia, Panagiota; Sandhu, Sophia; Xekouki, Paraskevi (Frontiers in Endocrinology, 2024)
Controversy exists over puberty suppression (PS) in adolescents with gender dysphoria (GD). PS is preferentially achieved with GnRH analogues. By preventing the development of secondary sex characteristics, PS may improve psychological functioning, well-being, quality of life, emotional and behavioral (especially internalizing) problems and depressive symptoms, thus decreasing suicidality. PS can also extend the diagnostic period and give transgender adolescents time to explore their gender identity. GnRHa may also decrease the need for feminization/masculinization surgery. However, 2-year treatment with GnRHa may result in bone mass accrual retardation (decrease in BMD/BMAD z-scores), growth velocity deceleration (decrease in height SDS), increase in fat mass, temporary pause in oocyte/sperm maturation. The most common side effects of GnRHa are hot flashes, mood fluctuations, fatigue and headache. They are usually mild and rarely lead to GnRHa discontinuation. Based on current scientific evidence, PS could be recommended to adolescents who meet the diagnostic criteria of gender incongruence (by DSM-5 and/or ICD-11) and have long-lasting intense GD, which aggravates with puberty onset. Before initiating PS, possible mental issues should be addressed and informed consent (by the adolescent/caregiver) should be given, after counseling on probable reproductive effects of GnRHa. GnRHa can only be started after the adolescent has entered Tanner stage 2. Nevertheless, published studies are inadequate in number, small in size, uncontrolled and relatively short-term, so that it is difficult to draw safe conclusions on efficacy and safety of GnRHa. Large long-term randomized controlled trials are needed to expand knowledge on this controversial issue and elucidate the benefit and risks of PS.